Rehabilitasi dan Rekonstruksi Bidang Perumahan dan Pascabencana Tsunami Pandeglang untuk Pemulihan Kehidupan Masyarakat Terdampak - Yulianto, Sugeng; Bahar, Fauzi; Pranoto, Sugimin (Universitas Budi Luhur, 2023)
The construction of permanent housing in Pandeglang District is classified as very fast with very good building construction when compared to development in other regions in Indonesia. Thus, this study aimed to analyze the post-tsunami rehabilitation and reconstruction in Pandeglang District in the infrastructure and housing sectors in terms of coordination, financing, and community empowerment. This research used a descriptive qualitative method. The results showed that post-tsunami recovery in the infrastructure and housing sectors had good diagonal coordination between units with different functions and levels. Coordination is carried out starting from the planning, budgeting, implementation, and evaluation stages. In the financing aspect, the optimization of the infrastructure sector is constrained by budget constraints, while in the housing sector, financing comes from grants and the central government's budget. Community empowerment in the infrastructure sector is limited to the aspect of supervision, which is different from the housing sector, which uses the pattern of community groups starting from the planning, implementation, and supervision stages. The infrastructure sector has not optimally supported the recovery of the lives of the affected communities in Pandeglang District. The housing sector recovered within 3 years after the Sunda Strait Tsunami disaster with the added value of the status of houses becoming property rights, sturdy buildings modeled on the Instant Steel Frame House (Rumah Instan Struktur Baja - RISBA), facilities for bathing, washing, latrines, and waste disposal facilities.